A Conceptual Study of Lifestyle Disorders w.s.r. to Raktagata Vata (Hypertension) - Verma, Priyanka; Sewda, Rahish; Prajapat, Monika; Sharma, Ashok Kumar; Sharma, Kishori Lal (International Research Journal of Ayurveda & Yoga, 2023)
A person’s lifestyle is essentially the result of their physical and psychological capabilities working together. This lifestyle is manifested in their habits, behaviour, diet and way of life and is based on the training they received as children from their parents, siblings, peer and other close family members. As a result, it requires purely psychological and natural control over the activities of the body and senses. This behaviour was described by Ayurveda as "Pragyaparadha" (intellectual blasphemy), one of the three fundamental causes of any ailment. As a result of Pragyaparadha, numerous inappropriate behaviours that are the underlying causes of different ailments, like Pragyaparadha is a tendency of repressing any natural need, which is identified as the root of roughly 50% of disorders. The fundamental cause of a disease is the reversal of any neurotransmission or inappropriate elimination of the waste products created during metabolism, which results in an accumulation of toxins. Therefore, one of the main causes of lifestyle disorders can be attributed to the habit of suppressing urges in an unhealthy lifestyle. To understand the physiology of blood pressure and the etio-pathogenesis of hypertension from the perspective of Ayurveda, a thorough examination of the existing Ayurvedic literature was conducted. According to one theory, hypertension should be viewed as the Prasara-Avastha, which refers to the spread of vitiated Doshasfrom their specific places, specifically of Vyana Vata, Prana Vata, Sadhaka Pitta, and Avalambaka Kapha along with Rakta in their disturbed phases.